Substitution of fat with various types of squashes and gourds from the cucurbitaceae family in the production of low-fat buffalo meat patties - Shamsol Kahar, Siti Nurjawaher; Ismail-Fitry, Mohammad Rashedi; Mat Yusoff, Masni; Rozzamri, Ashari; Bakar, Jamilah; Wan Ibadullah, Wan Zunairah (Malaysian Society of Applied Biology, 2021)
This study aimed to produce buffalo patties formulated with different types of squashes and gourds as fat substitutes. Kabocha squash, butternut squash, chayote squash, snake gourd and bottle gourd from the Cucurbitaceae family were used as the fat substitutes and buffalo meat patties with animal fat were the control. All patties were analysed and statistically compared in terms of physical properties and sensory acceptance. Generally, the moisture content, water holding capacity, cooking yield significantly increased for all samples compared to the control. The fat content reduced significantly below 3% for all fat-substituted patties, thus they can be regarded as low-fat. All fat-substituted samples were lighter in colour, with a harder texture than the control but the sensory analysis showed that the colour, texture, juiciness, flavour and overall acceptability of the fat-substituted patties were no different from the control. In conclusion, all the squashes and gourds tested were suitable as fat substitutes to produce low-fat buffalo patties, with chayote squash having the highest potential.